Superior cluneal nerve entrapment syndrome: a common but often overlooked cause of low back pain - Junki Mizumoto (Journal of General and Family Medicine, 2022)
Abstract An 81‐year‐old woman complained of low back pain (LBP) on her regular check‐up. Physical examination revealed tenderness at the middle point of the posterior iliac crest and burning dysesthesias around the tenderness point, without any other neurological findings. An injection of local anesthetics diminished the pain. The diagnosis of superior cluneal nerve entrapment syndrome (SCNES) was made. SCNES is relatively common, as high as 14% in patients with LBP, but frequently overlooked. Primary care physicians should be aware of the typical findings of SCNES for correct diagnosis and treatment.